Consumer Behaviour in Rural Markets : A-B-C-D Paradigm and its Applications - Rani, Sakthivel (Indian Journal of Marketing, 2010)
According to the census of India, villages with clear surveyed boundaries not having a municipality, corporation or board, with density of population not more than 400 sq. km and with at least 75 percent of the whole working population engaged in agriculture and allied activities would qualify as rural markets. According to this definition, there are 585, 764 villages in the country. Of these, only 0.5 percent have a population above 10,000. Around 50 percent of the villages have population between 200 and 1,000 and another 18 percent have a population less than 200. For FMCG and consumer durable companies, any territory that has more than 20,000 and 50,000 population respectively is a rural market. According to them, it is the class-II and III towns that are rural. According to the census of India 2001, there are more than 4,000 towns in the country. The census classified them into six categories-around 40-0 class-I towns with one lakh and above population (these are further classified into 35 metros and the rest, non-metros), 498 class-II towns with 50,000-99,999 population, 1,368 class-III towns with 20,000-50,000 population, 1,560 class-IV towns with 10,000-19,999 population. It is mainly the class-II and III towns that marketer's term as rural and that partly explains their enthusiasm about the so-called "immense potential" of rural India.